"I am stuck in the crime repetition and I dont wish this life": Exploring the recidivism factors of homeless recidivist women in Jalan Chow Kit, Kuala Lumpur - Jasni, Mohd Alif; Wan Jaafar, Wan Munira; Zainalaludin, Zumilah (Human Resource Management Academic Research Society (HRMARS), 2023)
Homeless recidivist women are a vulnerable community who end up on the streets due to failure to reintegrate. Returning to community life with a lack of resources and the absence of a support system causes them to return to criminal behavior, being re-arrested and returned to prison. Various risk factors that exist can influence these homeless recidivist women to be exposed to recidivism activities. A qualitative study using a phenomenological design was conducted and eight homeless recidivist women around Jalan Chow Kit were interviewed. The research findings led to the discovery of two main themes namely; personal factors and structural factors which notably influence the re-involvement of homeless recidivist women in criminal activities. The findings contribute to the knowledge related to homeless recidivist women based on gender aspects. This includes awareness to government agencies and stakeholders to provide post-release and extended care programs that could intervene the recidivism factors to avert homeless recidivist women from a life of crime, to become productive and law-abiding individuals. Keywords: Recidivist homeless women, recidivism factors, gender and reintegration